2019
DOI: 10.3389/fphar.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Actions of Tropeines on the α3 Glycine Receptor Function

Abstract: Glycine receptors (GlyRs) are chloride-permeable pentameric ligand-gated ion channels. The inhibitory activity of GlyRs is essential for many physiological processes, such as motor control and respiration. In addition, several pathological states, such as hyperekplexia, epilepsy, and chronic pain, are associated with abnormal glycinergic inhibition. Recent studies have pointed out that positive allosteric modulators targeting the GlyR α3 subunit (α3GlyR) displayed beneficial effects in chronic pain models. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Critical for the interaction of propofol To highlight the relevance of inter-subunit binding sites, models showing the interface of two adjacent α3 subunits are also shown. The interaction of tropisetron with the orthosteric site of α3 GlyRs was modeled according to [44]. The AM-3607 binding site was reconstructed as described in [11].…”
Section: Synthetic Glycine Receptor Modulators With Potential Analgesic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical for the interaction of propofol To highlight the relevance of inter-subunit binding sites, models showing the interface of two adjacent α3 subunits are also shown. The interaction of tropisetron with the orthosteric site of α3 GlyRs was modeled according to [44]. The AM-3607 binding site was reconstructed as described in [11].…”
Section: Synthetic Glycine Receptor Modulators With Potential Analgesic Effectsmentioning
confidence: 99%
“…The effects of tropeines have been mainly explored on α1 GlyRs, and less in α3 GlyRs. A recent report explored the modulation of homopentameric α3 GlyRs by tropeines [44]. Tropisetron did not potentiate α3 GlyRs, but rather caused concentration-dependent inhibition in the low micromolar range.…”
Section: Other Compounds With Modulatory Actions At Glycine Receptorsmentioning
confidence: 99%
“…All PAMs of GlyRs exhibit advantageous activities in the treatment of neuropathic pain. Very recently, Martín et al reported that tropisetron dose-dependently inhibited glycine-induced currents of α3 GlyRs, indicating that tropisetron is a NAM of the receptor . Molecular docking simulations predicted a tropisetron binding site next to the orthosteric sites in the ECD of α3 GlyRs.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 99%
“…Very recently, Marti ́n et al reported that tropisetron dose-dependently inhibited glycineinduced currents of α3 GlyRs, indicating that tropisetron is a NAM of the receptor. 82 Molecular docking simulations predicted a tropisetron binding site next to the orthosteric sites in the ECD of α3 GlyRs. Additionally, tropisetron acted as a PAM and NAM of α1 and α2 GlyRs, respectively.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 99%
“…It potentiated α1 GlyR-mediated currents in HEK293 cells at femto- to nanomolar concentrations but was an inhibitor at micromolar concentrations. , α3 GlyRs in HEK293 cells were inhibited by micromolar concentrations of tropisetron, and no potentiation was observed. A binding site for tropisetron in the open conformation of the receptor protein was proposed by structure modeling. , 3α-(3′-Methoxy-benzoyloxy)­nortropane (MBN) was identified as modulator of glycine- and taurine-induced GlyRs currents in Xenopus laevis oocytes. Several substitutions around the agonist binding site of the α1 interface were investigated .…”
Section: Modulators Of the Inhibitory Glycine Receptormentioning
confidence: 99%